Combined convection in inclined porous lid-driven enclosures with sinusoidal thermal boundary condition on one wall - Öztop, Hakan Fehmi; Varol, Asaf (Inderscience Enterprises Ltd, 2009)
A numerical study has been performed to obtain combined convection field in an inclined porous lid-driven enclosures heated from one wall with a non-uniformly heater. The lid moves at constant speed and temperature. Darcy-Brinkman-Forchheimer model was adopted to write governing equations and they solved using finite volume method. A detailed parametric study has been presented for different Reynolds numbers (10 <= Re <= 1000), Grashof numbers (10(4) <= Gr <= 10(5)), Darcy numbers (0.01 <= Da <= 0.1), porosity (0.6 <= epsilon <= 0.9) and inclination angle of enclosure (0 degrees <= phi <= 180 degrees). It is observed that flow field, temperature distribution and heat transfer are affected by inclination angle of the enclosure.
Keywords: porous medium; mixed convection; porosity; lid-driven